A person’s autonomy vis-à-vis the right to life does not include the right to be killed by a third person: assistance request to commit suicide and Diane Pretty’s case - Vivanco Martínez, Ángela (Acta Bioethica, 2002)
The author of this monograph analyses the resolutions pronounced by the House of Lords and by the EuropeanCourt of Human Rights in the case of Diane Pretty, an English citizen who died in may 2002. Because of a degenerative and incurable disease she pretended her husband be granted immunity if he helped her to commit suicide. The verdicts which were examined rejected her request.